Perbandingan Penggunaan Bahan Bakar High Speed Diesel Dan Biosolar Terhadap Emisi Gas Buang - Wahjono, Hari Boedi; Rozaq, Fadli (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2018)
Locomotives use diesel engines as a source of driving force, so the fuel used for this locomotive is to use diesel fuel or diesel oil. The purpose of this study is to determine the differences in the use of Biosolar fuel and HSD on exhaust emissions. This research is a descriptive quantitative research that aims to test the hypotheses of the data that have been collected in accordance with previous theories and concepts. Data collection method is by testing diesel engine vehicles and gas analyzers to measure opacity. Data analysis methods used are: descriptive analysis and T-test. The results showed that there were no statistically significant differences in the use of Biosolar fuel and HSD on exhaust emissions.